2015
DOI: 10.1371/journal.pone.0136903
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus in Cambodia: Prevalence among the General Population and Complete Genome Sequence of Genotype 4

Abstract: Hepatitis E virus (HEV) is a growing public health problem in many countries. In this study, we investigated HEV seroprevalence among the general population in the Siem Reap province, Cambodia, and performed HEV genetic analysis with the aim to develop an HEV prevention strategy. This seroepidemiological cross-sectional study conducted from 2010 to 2014 included 868 participants from four different locations in Siem Reap province, Cambodia. They answered questionnaires and provided blood samples for the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
(51 reference statements)
2
15
1
Order By: Relevance
“…With an IgG seroprevalence of 51.8%, HEV is hyperendemic in the rural population at least in Vientiane Capital. In South‐East Asia, seroprevalence rates between 8.9% and 77.7% have been reported (Gonwong et al, ; Holt et al, ; Sa‐nguanmoo et al, ; Yamada et al, ). This wide range certainly reflects regional differences and differing cohort selection criteria, but also disparities in sensitivity and specificity between commercial antibody detection kits (Avellon, Morago, Garcia‐Galera del Carmen, Munoz, & Echevarria, ; Vollmer, Diekmann, Eberhardt, Knabbe, & Dreier, ; Wenzel, Preiss, Schemmerer, Huber, & Jilg, ).…”
Section: Discussionmentioning
confidence: 99%
“…With an IgG seroprevalence of 51.8%, HEV is hyperendemic in the rural population at least in Vientiane Capital. In South‐East Asia, seroprevalence rates between 8.9% and 77.7% have been reported (Gonwong et al, ; Holt et al, ; Sa‐nguanmoo et al, ; Yamada et al, ). This wide range certainly reflects regional differences and differing cohort selection criteria, but also disparities in sensitivity and specificity between commercial antibody detection kits (Avellon, Morago, Garcia‐Galera del Carmen, Munoz, & Echevarria, ; Vollmer, Diekmann, Eberhardt, Knabbe, & Dreier, ; Wenzel, Preiss, Schemmerer, Huber, & Jilg, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, two recent studies revealed high HEV prevalence rates among general populations, including cases of early HEV infection and the presence of Genotypes 3 and 4 . Here, we investigated the HEV antibody prevalence and HEV RNA frequency in Cambodian blood donors.…”
mentioning
confidence: 95%
“…[25][26][27][28] And in humans, genotype 3 have also been found. [19][20][21][22][23][24] The seroprevalence of HEV, defined in this paper as the presence of anti-HEV immunoglobin G, was found to be 14% nationally in 2007-2008, but the seroprevalence was not homogenous, varying greatly within the country. 29 The study found lower HEV seroprevalence in Muslim dominated regions where pork consumption is relatively scarce.…”
Section: Epidemiologymentioning
confidence: 76%
“…17,18 However, recent evidence found conflicting results suggesting that those previous studies may be outdated. [19][20][21][22][23][24] The prevalent genotype of HEV is largely unclear and varies greatly by countries.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation